Clustering of Endorsements of Techniques of Neutralization as Predictors of Offending Among College Students: A Latent Profile Analysis Approach - Wojciechowski, Thomas (Criminal justice review, 2021)
Past research has provided evidence that techniques of neutralization may be used to rationalize offending, and individuals who endorse such rationalizations demonstrate greater offending risk. However, there is a dearth of research focused on how the endorsement of multiple techniques of neutralization may cluster together within an individual. There is also little understanding of how different clusters predict offending risk. The present study utilized data from 248 undergraduate students. Latent profile analysis was utilized to identify unobserved clusters of stronger/weaker endorsement of techniques of neutralization. Logistic regression was utilized to model the impact of differential clustering to predict offending risk. Results indicated that a five-profile solution best fits the data (low, responsibility deniers, moderate, victim deniers, and high). Participants assigned to the high profile demonstrated elevated offending risk relative to participants assigned to any of the other profiles. Participants assigned to the high profile reported relatively high endorsement of all techniques of neutralization but especially appeal to higher loyalties and denial of injury. Identification of college students demonstrating endorsement of techniques of neutralization consistent with the high profile should be targeted for intervention. Mentoring programs that take a social learning theory approach may be useful in this regard.